Red Bull PET/CT - Serfling, Sebastian E; Buck, Andreas; Rowe, Steven P; Higuchi, Takahiro; Werner, Rudolf (Nuklearmedizin - NuclearMedicine, 2023)
We report on a patient diagnosed with Hodgkin Lymphoma who was scheduled for [18F]FDG PET/CT as part of routine follow-up after treatment with two cycles of chemotherapy and mediastinal external beam radiation. Although the patient was advised to fast for at least four hours, an energy drink (Red Bull ) was ingested right after radiotracer administration, which led to increased uptake in the large skeletal muscles, thereby rendering this scan as non-diagnostic. After strictly following respective dietary recommendations, the repeated scan then provided excellent image quality and revealed response to treatment. In the present case report, we discuss the impact of major ingredients (sugar, caffeine, taurine, glucuronolactone) of Red Bull on large muscle uptake, which may also apply to “sugar-free” types of this popular energy drink. Moreover, this case reports demonstrates the importance to inform patients that they should avoid intake of energy drinks not only prior to but also after injection of [18F]FDG.
Keywords: Red Bull; Energy Drink; taurine; [18F]FDG